Design of a C‐band miniaturized rectifying circuit with a multilayer structure. Issue 7 (16th May 2017) - Feng, Xiaoping; Huang, Kama; Liu, Yilin
Abstract: This article proposes a novel concept for constructing a microwave (MW) rectifying circuit by using a multilayer structure, aiming at reducing physical dimensions. Specifically, an embedded via‐hole with connection of conductor layers in the multilayer structure is designed. A full‐wave electromagnetic analysis is carried out to study the impacts of various via‐hole design parameters. Then, a C‐band rectifying circuit based on HSMS‐286C Schottky diode is fabricated with the proposed multilayer structure for demonstration. The maximum MW‐DC conversion efficiency of 61% has been measured. In comparison with the counterpart, namely a conventional microstrip rectifying circuit, the proposed multilayer circuit shows a great reduction of physical dimensions and a very similar efficiency, which validates that the proposed circuit can reduce physical dimensions significantly without sacrificing the MW‐DC conversion efficiency.